The changing agenda of Israeli sociology : theory, ideology, and identity - Ram, Uri. (Albany : State University of New York Press, 1995)
Offers the first systematic and comprehensive overview of sociological thought in Israel, and pleads for a new agenda that would shift the focus from nation building to democratic and egalitarian citizenship formation.
""A Late Instance of European Overseas Expansion"" Colonization -- Conclusion Sociology in Society -- Back Matter -- EPILOGUE: Towards a Post-Zionist Sociology -- BIBLIOGRAPHY -- INDEX -- Back Cover.
Includes bibliographical references (pages 209-228) and index.
Print version record.
English.
JSTOR
Keywords: Sociology -- Israel; Israel -- Politics and government; Sociologie -- Israël.; Israël -- Politique et gouvernement; SOCIAL SCIENCE -- Regional Studies; SOCIAL SCIENCE -- Anthropology -- General; Politics and government; Sociology; Israel; Sociologie; Maatschappij; Israël (staat)